2011
DOI: 10.1088/0004-637x/738/1/59
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Structure of Low-Density Exo-Neptunes

Abstract: Kepler has found hundreds of Neptune-size (2-6 R ⊕ ) planet candidates within 0.5 AU of their stars. The nature of the vast majority of these planets is not known because their masses have not been measured. Using theoretical models of planet formation, evolution and structure, we explore the range of minimum plausible masses for low-density exo-Neptunes. We focus on highly irradiated planets with T eq ≥ 500 K. We consider two separate formation pathways for low-mass planets with voluminous atmospheres of ligh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
334
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(360 citation statements)
references
References 54 publications
26
334
0
Order By: Relevance
“…However, the above solution exhibits strong self-consistency between different determinations of some of the variables: the stellar mass from the spectroscopy agrees with the stellar mass from the dynamical modeling, and the semi-major axes from the light curve fitting + stellar model agree with the semi-major axes from dynamical model. From a theoretical stand point, Rogers et al (2011) attempted to put limits on the masses of similarly sized Kepler candidates and found that even low-mass low-density planets were possible in the general framework of core-nucleated accretion using plausible disk configurations. They found that a planet with a radius of 6 R ⊕ like Kepler-87 c and an equilibrium temperature of 500 K would have a mass of 6.4 M ⊕ if ≈20% of its mass were made of a gaseous envelope (assuming an ice-rock interior, and H/He in protosolar proportions).…”
Section: Discussionmentioning
confidence: 99%
“…However, the above solution exhibits strong self-consistency between different determinations of some of the variables: the stellar mass from the spectroscopy agrees with the stellar mass from the dynamical modeling, and the semi-major axes from the light curve fitting + stellar model agree with the semi-major axes from dynamical model. From a theoretical stand point, Rogers et al (2011) attempted to put limits on the masses of similarly sized Kepler candidates and found that even low-mass low-density planets were possible in the general framework of core-nucleated accretion using plausible disk configurations. They found that a planet with a radius of 6 R ⊕ like Kepler-87 c and an equilibrium temperature of 500 K would have a mass of 6.4 M ⊕ if ≈20% of its mass were made of a gaseous envelope (assuming an ice-rock interior, and H/He in protosolar proportions).…”
Section: Discussionmentioning
confidence: 99%
“…Detailed modeling of the internal structure of the Earth-sized planet Kepler-101c is not possible because of the weak constraint on its mass of M p < 3.8 M ⊕ (<8.7 M ⊕ ) at 1σ (2σ). We are only able to exclude a composition of pure iron with a probability of 68.3%, according to the models for solid planets by Seager et al (2007) and Zeng & Sasselov (2013), and any H/He envelope from the planetary radius constraint (Rogers et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly true for gas giant planet formation, with the final mass of the giant planet closely linked to the gas dispersal time (e.g., Lissauer et al 2009, Movshovitz et al 2010, Rogers et al 2011.…”
Section: Gas Diagnostics Of Photoevaporationmentioning
confidence: 99%